Impact of Social Media Quality and Brand Awareness on Purchase Decision Mediated by Role of Brand Image - I Gusti Agung Ayu Mas Suariedewi; I Gusti Ayu Athina Wulandari (Universitas Airlangga, 2023)
Background: Social media's digital technology revolution has already taken place and is steadily altering consumer expectations and behavior. Currently, social media is used as a strategic communication tool by many corporate divisions. Consequently, social media as a collection of online media platforms, offers new opportunities for both individuals and organizations focused on business to promote and express their values to their target audience. Objective: The study aims to elucidate the impact of social media quality and brand awareness on purchase decisions, with brand image serving as a mediating variable. Method: The sampling technique in this research uses a purposive sampling method and a questionnaire instrument for data collection. The study included a sample of 100 respondents and was conducted on all Endek customers who purchase clothing from Galeri Endek and live in Denpasar City. The quantitative Partial Least Square (PLS) approach is the analytical tool that is employed. Results: The findings show that social media quality and brand awareness has a significant positive influence on brand image. Brand image has a statistically significant positive influence on purchase decisions, however social media quality has no statistical significance on purchase decisions. Additionally, social media quality influences consumer purchase decisions in a notable and positive way, with some degree of the brand image serving as a partial mediator. Conclusion: The contribution of the research findings suggested that Galeri Endek Bhumimi could potentially enhance its brand awareness and brand image by expanding its use of social media. Galeri Endek Bhumimi should improve their social media quality so that it can improve brand image and have an impact on purchasing decisions. The empirical evidence suggests that the selection of products by consumers is impacted by their recognition and perception of the brand. Keywords: brand awareness, brand image, purchase decision, social media quality